Dongeng Masyarakat Kabupaten Kampar dalam Kajian Sastra Ekologis - Nelfita, Yulia; Hidayat, Rian; Yulantomo, Aris (Innovative: Journal Of Social Science Research, 2025)
This research is titled Fairy Tales of Kampar Regency In Ecological Literature Studies. Literature is closely related to the human environment, as well as folklore in Naga Beralih Village which is dominated by stories set in nature. This research seeks to analyze the ecological elements contained in the Kampar Regency Folklore. This research is descriptive qualitative with literary and folkloric ecological approach. The story studied was taken as a sample with consideration to represent the ecological background that exists in the collection of The Dragon Switch folklore. The results showed that ecological elements are inseparable from the lives of kampar people. This is illustrated from the ecological elements raised in his folklore. Based on the whole discussion conducted in the analysis section, it can be concluded that the fairy tale Naga Switch Kampar Society contains ecological literary concepts according to Garrard. The concept includes pollution, disasters, animals, and the earth. Fairy tales need good documentation so as not to become extinct or not recognized as belonging to other nations. Behind its simple form, fairy tales can teach many good things to form one's character including forming an environmentally caring character.